An Assessment study of the international in football refereeing to Arbel - Qasem, Sabah (Journal of Physical Education, 2010)
This study aims to show the importance of such courses in updating the referees information regarding the new changes and modifications of the law. In order to reach appoint where he could deal with the essence of the law. The Iraqi referee was secluded by FIFA for many years the lack of new information and new means of teaching which could clarify points in the law made it difficult to develop referee and affected their performance. The study aims at knowing the novelty of the information obtained by participants the level of its effect and positive aspects of the course in addition to the measures of elevating then. The researcher assumed that there were an aspect of novelty in the information obtained by participants The sample consisted of 40 referees who answered the assessment form which included the opinions of experts 16 points. The researcher drew that the information and the means of converting it were novel and that the Iraq referee suffers a shortage in referencing courses helping in specifying and polishing his information